The COVID-19 pandemic in Binmaley changes in spaces, experience of religion, and faith expressions - Diaz, Rizelle A.; Medina, Maria Cecilia T. (Quezon City Asian Center, University of the Philippines Diliman, 2023)
This thesis analyzes how COVID-19 public guidelines have affected people's experience of religion. It looks into the changes in the space, territory, and faith expressions of the parish church community in Binmaley, Pangasinan. Through these three concepts, the thesis recognizes the parish as thirdspace. Edward Soja's (1996, p.73) thirdspace asserts that "we are ... historical-social-spatial beings, actively participating individually and collectively in the construction/production - "The becoming" - of histories, geographies, societies. Interpreting Soja's (1996, P. 71) thirdspace, the trialectic of spatiality-historically-sociality, the study denotes spatiality as space, historicality as memory, and sociality as faith expressions.

Through these interconnected concepts, changes in space due to COVID-19 guidelines have affected the way people remembered and experienced the parish church. In terms of space, the parish church functioned as religious space (center of faith) and public space was decentralized--accessed from a distance or through digital screens. In terms of memory, the parish church was seen as a community and sacred space. During the pandemic, the parish church as memory has shifted to smaller units (individual or family) and to a distanced distracting space (e.g. outdoors or at home). In faith expressions, the individual often expresses their faith as working towards an individual need (penance or blessing). On the other hand, the community expresses its own faith as a way to respond to God's call. Both convey their faith proactively. With the pandemic, both faith expressions --individual and communal -- felt too passive for the respondents. Socially, distanced and online/virtual religious practices have stripped respondents of their initiative and duty. In the end, respondents claimed an "incomplete" experience of religion during the COVID-19 pandemic. --Provided by the author
Thesis (Master of Arts in Philippine Studies) -- University of the Philippines Diliman
Keywords: COVID-19 Pandemic, 2020-; COVID-19 (Disease) -- Religious aspects -- Catholic Church; COVID-19 (Disease) -- Philippines -- Binmaley (Pangasinan)